KAJIAN ASUHAN KEBIDANAN PADA IBU NIFAS NY. A UMUR 17 TAHUN PIA0 DENGAN POST PARTUM BLUES DI SRAGEN - Fitriyya, Munaaya; ., Yuliana (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
In Indonesia, namely in Jakarta 25% of 580 mothers who become respodennya have syndrome. And from several studies that have been done in Jakarta, Yogyakarta, and Surabaya, it was found that the number of baby blues syndrome incidence is 11-30% is a number that is not small and can not be left alone.Labor becomes the culmination of pregnancy to be passed from all pregnancy processes. There are various feelings that mix together when welcoming labor. Among the happy because it will soon see and meet with the baby, then generally pregnant women are also anxious. Postpartum will surely come feelings in a mother feel happy, happy and at the same time relieved because of struggle during 9 months during pregnancy and childbirth process has passed safely. Now comes the baby who will always accompany the mother's day. But almost 50-80% of feelings of joy that descend now turn into a feeling of sadness and worry, this happens because the body is undergoing major physical changes after giving birth, the hormones in the body will also undergo major changes and have just experienced a labor process exhausting, feelings of sadness and depression and tend to be worse around the third or fourth day after after giving birth. Research Objectives: Conducting midwifery studies on Nifas Ny's mother. A 17-Year-Old Age with Post Partum Blues. This data collection using primary and secondary data collection techniques with data collection through interview, observation, examination and documentation. Implementation of midwifery care using 7 steps Varney. Midwifery care has been performed for 3 days carried out midwifery care for 3 days of good motherhood, mother is not worried, usually sleep, want to eat, and feeling happy. The results of the assessment, monitoring, implementation, action plan on postpartum mothers with post partum blues no gap between the theory and the case for three days the patient is in good condition. Keywords: Midwifery Care, Postpartum, Post Partum Blues